PESANTREN, KYAI DAN TAREKAT DALAM TRANFORMASI SOSIAL - Muhammad Fauzi (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2015)
Pesantren has a long history associated with its functions as a forum to educate satri in religious sciences. The central figure is a boarding school clerics who became leader of the school and have the authority which determines the dynamics of intellectual santrinya, even the surroundings.Lately there is a tendency to expand the functions of pesantren not only as a religious institution, but also as a social institution. Consequently, the task is not only working on matters of religion, but also menangggapi social problems. Social work initially may be a side job or a "surrogate" of outsiders boarding. But then, social work makes boarding trusted by many parties as agents bring significant social change. Because they assume, almost all of the functional components of schools have links with the community, ranging from the influence of clerics, religious teacher and his students that provide color in the middle of society. Pesantren is a unique Islamic institution and have a different culture from other Islamic educational institutions